Association Between Vascular Access Dysfunction and Subsequent Major Adverse Cardiovascular Events in Patients on Hemodialysis: A Population-Based Nested Case–Control Study. Issue 26 (July 2015) - Kuo, Te-Hui; Tseng, Chien-Tzu; Lin, Wei-Hung; Chao, Jo-Yen; Wang, Wei-Ming; Li, Chung-Yi; Wang, Ming-Cheng
Abstract : Abstract: The association between dialysis vascular access dysfunction and the risk of developing major adverse cardiovascular events (MACE) in hemodialysis patients is unclear and has not yet been investigated. We analyzed data from the National Health Insurance Research Database of Taiwan to quantify this association. Adopting a case–control design nested within a cohort of patients who received hemodialysis from 2001 to 2010, we identified 9711 incident cases of MACE during the stage of stable maintenance dialysis and 19, 422 randomly selected controls matched to cases on age, gender, and duration of dialysis. Events of vascular access dysfunction in the 6-month period before the date of MACE onset (ie, index date) for cases and before index dates for controls were evaluated retrospectively. The presence of vascular access dysfunction was associated with a 1.385-fold higher odds of developing MACE as estimated from the logistic regression analysis. This represents a significantly increased adjusted odds ratio (OR) at 1.268 (95% confidence interval [CI] = 1.186–1.355) after adjustment for comorbidities and calendar years of initiating dialysis. We also noted a significant exposure–response trend ( P < 0.001) between the frequency of vascular access dysfunction and MACE, with the greatest risk (adjusted OR = 1.840, 95% CI = 1.549–2.186) noted in patients with ≥3 vascular access events. We concluded that dialysis vascular access dysfunction was significantly associated with an increased risk of MACE. Hence, vascular access failure can be an early sign for MACE in patients receiving maintenance hemodialysis. Active monitoring and treatment of cardiovascular risk factors and related diseases, not merely managing vascular access dysfunction, would be required to reduce the risk of MACE. Abstract : Supplemental Digital Content is available in the text